La mujer en la tradición del Discípulo Amado - Estévez López, Elisa 1958- (1994)
Análisis del papel preferencial que tiene la mujer en el cuarto Evangelio. Encuentro de Jesús con la samaritana, a quien se revela en forma personal y es constituida misionera. La confesión mesiánica de Marta, más importante que la de Pedro, es el fundamento de una Iglesia construida sobre el testimonio apostólico de una mujer. María de Betania anuncia la muerte y resurrección de Jesús. María Magdalena, enviada a evangelizar a los 12, es el primer y más destacado testigo de Jesús resucitado. La madre de Jesús, es la discípula que recorre el camino desde Israel (Bodas de Caná) hasta la Iglesia (al pie de la cruz). El artículo invita a repensar la eclesiología desde la mujer.
Analysis of the preferential role which women have in the fourth gospel. Encounter of Jesus with the Samaritan: he reveals himself to her in a personal way, and makes her a missionary. Martha’s confession of Jesus as Messiah —more important than Peter’s— is the basis of a church built on the apostolic testimony of a woman. Mary of Bethany announces the death and resurrection of Jesus. Mary Magdalene, sent to evangellize the twelve, is the first and most outstanding witness of the resurrected esus. The mother of Jesus is the disciple who follows the ath from Israel (the wedding at Cana) to the Church (at the oot of the cross). The article invites a rethinking of ecclesiology rom the point of wiew of women.